2021
DOI: 10.1613/jair.1.12618
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Local Search based on Dynamic Connectivity Maintenance for Minimum Connected Dominating Set

Abstract: The minimum connected dominating set (MCDS) problem is an important extension of the minimum dominating set problem, with wide applications, especially in wireless networks. Most previous works focused on solving MCDS problem in graphs with relatively small size, mainly due to the complexity of maintaining connectivity. This paper explores techniques for solving MCDS problem in massive real-world graphs with wide practical importance. Firstly, we propose a local greedy construction method with reasoning rule c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Heuristics, especially local search methods that move from solution to solution in the space of candidate solutions by applying local changes, play an important role in solving NP-hard problems. For the last decades, various heuristic algorithms have been proposed to find high-quality solutions for large-scale instances in an acceptable time and computer memory (Wang et al, 2017;Lu et al, 2020;Zhang et al, 2021;Lu et al, 2021;Bilandi et al, 2021). Among heuristic algorithms, tabu search (Glover, 1989(Glover, , 1990 and simulated annealing (Skiscim & Golden, 1983;Kirkpatrick et al, 1983), which solved many graph problems successfully (Palubeckis et al, 2014;Bilandi et al, 2021;Lu et al, 2019), showed their efficiency in solving many benchmark instances of the CPP.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Heuristics, especially local search methods that move from solution to solution in the space of candidate solutions by applying local changes, play an important role in solving NP-hard problems. For the last decades, various heuristic algorithms have been proposed to find high-quality solutions for large-scale instances in an acceptable time and computer memory (Wang et al, 2017;Lu et al, 2020;Zhang et al, 2021;Lu et al, 2021;Bilandi et al, 2021). Among heuristic algorithms, tabu search (Glover, 1989(Glover, , 1990 and simulated annealing (Skiscim & Golden, 1983;Kirkpatrick et al, 1983), which solved many graph problems successfully (Palubeckis et al, 2014;Bilandi et al, 2021;Lu et al, 2019), showed their efficiency in solving many benchmark instances of the CPP.…”
Section: Previous Workmentioning
confidence: 99%
“…For more detailed relationships of the configuration checking strategy and the tabu method, we refer to (Cai et al, 2011). The configuration checking strategy has proven effective to solve problems in graph theory and SAT problems Luo et al, 2013Luo et al, , 2015Wang et al, 2017;Zhang et al, 2021). The main idea of the configuration checking strategy is to prevent a stochastic local search algorithm from revisiting the same scenario by checking whether the states or neighbors' states of a vertex have changed or not.…”
Section: The Configuration Checking Strategymentioning
confidence: 99%
“…Zhang et al 28 explored techniques for solving minimum connected dominating set problems in massive real‐world graphs with wide practical importance. The authors implemented the local greedy construction method with a reasoning rule called 1hopReason.The advantages of this proposed method are a hybrid dynamic connectivity maintenance method and a novel fast connectivity maintenance method based on a spanning tree.…”
Section: Related Workmentioning
confidence: 99%